2007
DOI: 10.1094/pdis-91-10-1361c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Bacterial Leaf and Fruit Spot of Cashew Nut (Anacardium occidentale) Caused by Xanthomonas campestris pv. mangiferaeindicae in Brazil

Abstract: In 2003 and 2004, leaves and young fruits of cashew nut plants showing an undescribed disease symptom were observed on plants of an early-dwarf clone in a commercial orchard in Ceará and Piauí states in northeastern Brazil. Initial symptoms consisted of angular, water-soaked, dark-to-black spots on the leaf and at the mid-rib vein surrounding the leaf veins. Eventually, lesions also extended from the mid-rib to the secondary veins, delineating the vein system of the leaf. In young, green fruits, symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Subsequently, in 1999, Papa et al (15) observed the presence of the disease in Mato Grosso do Sul. From 2(X)3, in addition to the usual angular leaf spots, atypical spots have been observed in cashew leaves and fruits in the Brazilian states of Piauf, Ceará (29)(30)(31)(32), Minas Gerais (29,3O,. 'Í2), and Sao Paulo (8).…”
mentioning
confidence: 99%
“…Subsequently, in 1999, Papa et al (15) observed the presence of the disease in Mato Grosso do Sul. From 2(X)3, in addition to the usual angular leaf spots, atypical spots have been observed in cashew leaves and fruits in the Brazilian states of Piauf, Ceará (29)(30)(31)(32), Minas Gerais (29,3O,. 'Í2), and Sao Paulo (8).…”
mentioning
confidence: 99%
“…previously called X. campestris pv. mangiferae indicae [41] . Cashew bacterial blight is recognized by angular, dark to black and oily spots on the leaves with many along the veins.…”
Section: Fig1a: M Loripes Sourcementioning
confidence: 99%
“…It is also cultivated for the apple (cashew apple) which contains a sweet, acidic and astringent juice. This apple is directly transformed into juice, wine, syrup or beer in Burkina Faso, Senegal and Ivory Coast (Afouda et al, 2013) However, many problems are found in the chain of production of this crop, such as diseases caused by microorganisms, which in many cases are limiting their commercial exploitation (Assenga et al, 2020 ;Viana et al, 2007). Among these diseases, dieback is a common one in cashew orchads.…”
Section: Introductionmentioning
confidence: 99%